Effectiveness of Cognitive Processing Therapy and Prolonged Exposure in the Department of Veterans Affairs. Issue 2 (April 2018) - Rutt, Benjamin T.; Oehlert, Mary E.; Krieshok, Thomas S.; Lichtenberg, James W.
Objective: This study evaluated the effectiveness of cognitive processing therapy and prolonged exposure in conditions reflective of current clinical practice within the Veterans Health Administration. Method: This study involved a retrospective review of 2030 charts. A total of 750 veterans from 10 U.S. states who received cognitive processing therapy or prolonged exposure in individual psychotherapy were included in the study (participants in cognitive processing therapy, N  = 376; participants in prolonged exposure, N  = 374). The main dependent variable was self-reported posttraumatic stress disorder symptoms as measured by total scores on the Posttraumatic Stress Disorder Checklist. The study used multilevel modeling to evaluate the absolute and relative effectiveness of both treatments and determine the relationship between patient-level variables and total Posttraumatic Stress Disorder Checklist scores during treatment. Results: Cognitive processing therapy and prolonged exposure were equally effective at reducing total Posttraumatic Stress Disorder Checklist scores. Veterans who completed therapy reported significantly larger reductions in the Posttraumatic Stress Disorder Checklist than patients who did not complete therapy. There were no significant differences in the improvement of posttraumatic stress disorder symptoms with respect to age and three racial/ethnic groups (Caucasian, African American, and Hispanic). Conclusions: Cognitive processing therapy and prolonged exposure were shown to be effective in conditions highly reflective of clinical practice and with a highly diverse sample of veterans. Challenges related to dropout from trauma focused therapy should continue to be researched.